Development of Resin Handicrafts (Crude Oil Derivative Products) for Students at MTs Negeri 7 Kampar: Pembinaan Kerajinan Tangan Berbahan Resin (Produk Turunan Crude Oil) Bagi Peserta Didik di MTs Negeri 7 Kampar - Novrianti; Richa Melysa; Irwan Anwar; Teguh Sahibillah Alfajri; Ochi Willya Chevrananda (Journal of Community Service and Application of Science, 2023)
The program for promoting the creation of resin-based handicrafts (a byproduct of crude oil) is conducted at MTS Negeri 7 Kampar,  the village o Kuntu in the Kampar District. This village is known for being one of the places of religious tourism attraction, particularly the tomb of Syekh Burhanuddin. The community service activity (PKM) aims to introduce students to various resin-based handicrafts and to provide them with direct hands-on experience. The methods for this activity involve preparing equipment and materials and creating sample handicrafts at the Faculty of Engineering, Islamic University of Riau. The implementation includes educating and training the students, with evaluations carried out through pre-tests and post-tests to measure the students' knowledge improvement in relation to resin, as well as evaluating the success of the students' crafted handicrafts. The results of this community service activity have successfully increased students' knowledge and skills by 100%, as shown by a questionnaire survey conducted both before and after the resin-based handicraft creation mentoring.